Exploring the Experiences of Partners of Veterans with Mental health Difficulties Attending a Group Psychoeducation Support Intervention: A Qualitative Study. - Spencer-Harper Lucy; Turgoose David; Murphy Dominic (Journal of Family Medicine, 2019)
Background Research has demonstrated that partners living alongside veterans with mental health difficulties are at high risk of developing mental health difficulties themselves and secondary trauma. A variety of interventions have been developed to support partners. Research to date has relied on quantitative methodologies to evaluate the efficacy of such interventions with less emphasis on learning about the experiences of individuals on the courses. Objective The aim of this qualitative paper was to understand the experiences of partners who engaged in a five-week structured support intervention, ‘The Together Programme’ (TTP) which had been piloted across UK cities. This programme involved tailored psycho educational materials adapted to the needs of veteran’s partners living alongside PTSD. Further the potential mechanisms of change for participants engaged with the programme were explored as well as the impact of treatment on their relationships. Methods Eight female partners were recruited from an original sample of 57 partners who were intimate relationships with treatment seeking veterans with mental health difficulties. These participants had completed TTP. Qualitative data was collected using a semi structured interview and explored using Interpretative Phenomenological Analysis. Results Three key themes emerged from the data, these were self-growth, changing role in relationships and connecting with others. The themes included several sub themes. Self-growth sub-themes were mastering the ‘inner judge’, ‘confidence in ability to cope’ and ‘taking care of my needs’. Changing role in relationship sub-themes were ‘acceptance and understanding’ and ‘improved communication in relationship’. Connecting with others was described by the sub-themes of ‘knowing I am not alone’, ‘peer support’ and ‘hope’. Conclusions This study suggeststhere were three key areas where thestructured evidence-based support programme had an impact on participants experiences. These were factors that helped participants to normalise their experiences and increase participants understanding and interpersonal skills that promote changes in relationship functioning with the veteran.
Keywords: mental health